El léxico de la lengua Andaquí - Coronas Urzúa, Gabriela (Universidad de Costa Rica, 2015)
En este artículo se presenta un arreglo alfabético de todo el léxico de Andaquí (una lengua indígena colombiana extinta) contenida en dos documentos enviados a España durante la época colonial. Estos datos constituyen las únicas fuentes disponibles para analizar el lenguaje. El diccionario incluye dos partes: el vocabulario Andaquí-español y el vocabulario español-Andaquí. This article presents an alphabetical arrangement of the entire lexicon of Andaqui (an extinct indigenous Colombian language) contained in two documents sent to Spain during colonial times. These data constitute the only sources available to analyse the language. The dictionary includes two parts: the Andaquí-Spanish vocabulary and the Spanish-Andaquí vocabulary.